The association between blood glucose levels and matrix-metalloproteinase-9 in early severe sepsis and septic shock. Issue 1 (December 2016) - Sachwani, Gul; Jaehne, Anja; Jayaprakash, Namita; Kuzich, Mark; Onkoba, Violet; Blyden, Dione; Rivers, Emanuel
Abstract Background Hyperglycemia is a frequent and important metabolic derangement that accompanies severe sepsis and septic shock. Matrix-Metalloproteinase 9 (MMP-9) has been shown to be elevated in acute stress hyperglycemia, chronic hyperglycemia, and in patient with sepsis. The objective of this study was to examine the clinical and pathogenic link between MMP-9 and blood glucose (BG) levels in patients with early severe sepsis and septic shock. Methods We prospectively examined 230 patients with severe sepsis and septic shock immediately upon hospital presentation and before any treatment including insulin administration. Clinical and laboratory data were obtained along with blood samples for the purpose of this study. Univariate tests for mean and median distribution using Spearman correlation and analysis of variance (ANOVA) were performed. Ap value ≤ 0.05 was considered statistically significant. Results Patients were grouped based on their presenting BG level (mg/dL): BG <80 (n = 32), 80–120 (n = 53), 121–150 (n = 38), 151–200 (n = 23), and > 201 (n = 84). Rising MMP-9 levels were significantly associated with rising BG levels (p = 0.043). A corresponding increase in the prevalence of diabetes for each glucose grouping from 6.3 to 54.1 % (p = 0.0001) was also found. As MMP-9 levels increased a significantly (p < 0.001) decreases in IL-8 (pg/mL) and ICAM-1 (ng/mL) were noted. Conclusion This is the first study in humans demonstrating a significant and early association between MMP-9 and BG levels in in patients with severe sepsis and septic shock. Neutrophil affecting biomarkers such as IL-8 and ICAM-1 are noted to decrease as MMP-9 levels increase. Clinical risk stratification using MMP-9 levels could potentially help determine which patients would benefit from intensive versus conventional insulin therapy. In addition, antagonizing the up-regulation of MMP-9 could serve as a potential treatment option in severe sepsis or septic shock patients.